Agriculture and rural society after the Black Death : common themes and regional variations / edited by Ben Dodds and Richard Britnell. - Dodds, Ben; Britnell, R. H. (Studies in regional and local history (Hertfordshire, England), 2008)
With special emphasis on the period following the Black Death, this new collection of essays explores agriculture and rural society during the late Middle Ages. Combining a broad perspective on agrarian problems, such as depopulation and social conflict, with illustrative material from detailed local and regional research, this compilation demonstrates how these general problems were solved within specific contexts. The contributors supply detailed studies relating to the use of the land, the movement of prices, the distribution of property, the organization of trade, and the cohesion of village society, among other issues. New research on regional development in medieval England and other European countries is also discussed.